Radiographic location of the femoral footprint of the cranial cruciate ligament in dogs - Bolia, A.; Winkels, P.; Böttcher, P. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2015)
Objective: To describe the radiographic location of the center of the femoral footprint of the cranial cruciate ligament (CrCL) in dogs. Material and methods: Using femora from 49 adult, orthopedically sound dogs (bodyweight ≥ 20 kg), a radiopaque marker was placed on the cranial border of the femoral footprint of the CrCL. Computed tomography and threedimensional (3D) reconstruction of each femur was performed subsequently, followed by manual segmentation of the footprint on the 3D models and calculation of its center. Finally, virtual digital radiographs in two planes were produced and the location of the calculated center of the CrCL was expressed using three different methods (4×4 box grid method and percentage position for the medio-lateral projection; o’clock position for the disto-proximal projection). Results: In the medio-lateral radiographs the center of the femoral footprint was consistently located in the second rectangle from the top of the most caudal column of the 4×4 grid. The mean percentage caudo-cranial and proximo-distal location was 20.2% (± 2.2) and 33.8% (± 3.7), respectively. In the disto-proximal radiograph, the o’clock position of the CrCL center was between 2 and 3 o’clock in 97.6% of cases. Conclusion: The radiographic location of the center of the femoral footprint can be consistently predicted in medio-lateral and disto-proximal stifle radiographs of dogs over 20 kg. Clinical significance: The reported data can be used to plan and verify the placement of the femoral tunnel opening for intra-articular anatomic CrCL repair.
Keywords: Stifle; cranial cruciate ligament; intraarticular repair